118‐year climate and extreme weather events of Metropolitan Manila in the Philippines. (23rd August 2019) - Bagtasa, Gerry
Abstract: Metropolitan Manila, the Philippines, is a megacity with a population of 12.9 million people. Unabated urbanization and disorganized infrastructure build‐up, coupled with a large urban poor population have made many of its population vulnerable to climate change. This study presents the 118‐year urban climate and extreme weather events of Metropolitan Manila. Daily average and minimum temperature are on the rise comparable to countrywide trends. Consequently, there are more warm and less cold nights. Total annual precipitation is also increasing at a rate of 77.99 mm/decade. Decreasing simple daily intensity index implies that higher observed precipitation is due to the increase in wet days count rather than intensity. Tropical cyclones (TCs) are critical in producing most extreme rainfall events in the metropolis. Extreme precipitation is induced either by a TC's immediate rainbands or remote precipitation effects by enhancing the prevailing summer monsoon flow. TC‐induced rain modulates annual rainfall variability and is estimated to contribute 45.2% to Metropolitan Manila mean total rainfall. Abstract : 118‐year urban climate and extreme weather events of Metropolitan Manila, the capital of the Philippines. Observed temperature and precipitation are rising in this megacity. Temperature is driven by large and small scale forcing (i.e., ENSO, urbanization) while precipitation is heavily influenced by landfalling and distant tropical cyclones.